Press Coverage of Terrorism Topics in The Iraqi Al-Mada Newspaper" an analytical study" (Damascus University Journal of arts and humanities sciences, 2024)
The study aimed to identify the types of press coverage of terrorism topics in the Iraqi Al-Mada newspaper, its objectives, reveal its trends and sources, as well as monitor the most prominent results resulting from terrorism, in addition to knowing the types of images used during the study period.The study used the media survey method, and data was collected through the content analysis tool, and a regular random sample was drawn using the industrial week.The results of the study showed that military operations ranked first in terms of the most prevalent topics, and the newspaper relied on superficial treatment in presenting issues related to terrorism. As news coverage ranked first, depending on the goal of the media, while topics dealing with awareness and education decreased; This indicates the absence of security awareness of issues related to terrorism.Which requires the newspaper to highlight it in order to play its role inreducing terrorism, and the newspaper headed towards the official government trend in obtaining information related to terrorism, and the social results emerged in the newspaper; It included the societal and family disintegration that occurred as a result of the spread of terrorism in Iraq for a long time, followed by a slight difference in the security effects, which the newspaper reflected through military operations, and the resulting insecurity and stability, while it was not interested in highlighting the media and religious effects, as it relied on extended headlines in publishing topics related to the phenomenon of terrorism and used objective images.
Keywords: Press Coverage; Terrorism; The Iraqi Al-Mada Newspaper